Conformational preference of bicyclic β‐amino acid dipeptides. Issue 6 (1st April 2020) - Otani, Yuko; Park, Seokhwi; Ohwada, Tomohiko
Abstract: Bridged bicyclic amino acids have high potential applicability as self‐organized, conformationally constrained synthetic building blocks that do not require assistance from hydrogen bond formation. We systematically investigated the intrinsic conformational propensities of dipeptides of bridged bicyclic β‐amino acids by means of accelerated molecular dynamics simulation and density functional theory (DFT) calculations in methanol, chloroform, and water. While the main‐chain conformation, represented by φ and θ values, is fixed by the nature of the bicyclic ring structure, rotation of the C‐terminal carbonyl group ( ψ ) is also restricted, converging to one or two minima. In endo ‐type dipeptides, in which the two N‐ and C‐terminal amides are spatially close to each other, the C‐terminal amide plane is placed horizontally. In exo ‐type dipeptides, in which the two amides are on opposite sides of the ring plane, the C‐terminal carbonyl group can take two types of positions: either parallel/antiparallel with the N‐terminal carbonyl or beneath the bicyclic ring, forcing the amide NHMe moiety to lie outside of the ring. We also examined the cis‐trans preference of model bicyclic amides. Although the parent amides exhibit cis‐trans equilibrium without any preference, addition of a methyl group on one of the bridgehead positions tips the equilibrium towards trans. Abstract :